2020
DOI: 10.5812/ijp.108416
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound and Radiography Evaluation of the Tips of Peripherally Inserted Central Catheters in Neonates Admitted to the NICU

Abstract: Background: Appropriate and accurate easy access tools are necessary to overcome complications from malpositioned line tips of peripherally inserted central catheters (PICCs) in critically ill neonates. Ultrasound is a radiationless, cost-beneficial, and time-saving method that allows medical personnel to manipulate the line and correct possible malposition of this tip. In addition, it reduces the need for a second radiography. Objectives: We compared the effectiveness of sonography with radiography for confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
40

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(43 citation statements)
references
References 30 publications
0
3
0
40
Order By: Relevance
“…The reference standard in six studies was solely chest radiography. In two studies the reference standard was both supine chest and abdominal radiography [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reference standard in six studies was solely chest radiography. In two studies the reference standard was both supine chest and abdominal radiography [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies documented that the reference test was reported incorrectly. These erroneous radiographic reports were ultimately corrected following the US examination, which demonstrated a more accurate tip position [ 36 , 38 40 ]. Radiographic misinterpretations in these four studies were a mixture of false reports of malposition and false reports of optimum position.…”
Section: Resultsmentioning
confidence: 99%
“…A amostra evidenciou que publicações com a temática abordada são em pequeno número. Neste estudo, dezessete publicações foram incluídas para revisão, sendo doze (70,6%) da PubMed (BARONE et al, 2022;BAYOUMI et al, 2022;FRIDOLFSSON, 2022;GRASSO et al, 2022;ROSSI et al, 2022;TU et al, 2021;SUELL et al, 2020;MOTZ et al, 2019a;MOTZ et al, 2019b;JOHNSON et al, 2016;NGUYEN, 2016;ABDEYAZDAN et al,2014) e dois (11,7%) da EMBASE (CASTRO et al, 2014;KADIVAR et al, 2020). LILACS (VILAR et al,2020), WOS (SINGH et al, 2020), BDTD (NEGRI, 2019) contribuíram com um (5,9%) estudo cada.…”
Section: Resultsunclassified
“…produções (BARONE et al, 2022;BAYOUMI et al, 2022;FRIDOLFSSON, 2022;GRASSO et al, 2022;ROSSI et al, 2022;TU et al, 2021;KADIVAR et al, 2020;SINGH et al, 2020;SUELL et al, 2020;VILAR et al,2020;MOTZ et al, 2019a;MOTZ et al, 2019b;NEGRI, 2019). O ano de 2016 se destacou com duas (11,8%) publicações (JOHNSON et al, 2016;NGUYEN, 2016), seguido de 2014, com duas (11,8%) (ABDEYAZDAN et al,2014;CASTRO et al, 2014).…”
Section: Resultsunclassified
“…As mentioned above, CXR has a number of disadvantages. To overcome these shortcomings, the ultrasound localization method has been gradually applied in clinical practice in recent years (3,4,(7)(8)(9)(10)(13)(14)(15), and studies or guidelines recommending ultrasound as the "gold standard" for determining the correct tip position have been developed (2)(3)(4).…”
Section: Discussionmentioning
confidence: 99%